INTRACAVERNOSAL INJECTION OF PLATELET-RICH PLASMA AS AN ALTERNATIVE TREATMENT OF ORGANIC ERECTILE DYSFUNCTION: A SYSTEMATIC REVIEW AND META-ANALYSIS OF RANDOMIZED CONTROLLED TRIALS - Rayyan, Muhammad Isra Rafidin; Kholid, Akbar Fakhrudin; Wahyudi, Septa Surya (Indonesian Urological Association, 2025)
Objective: To evaluate the effectiveness and safety of intracavernosal injections of platelet-rich plasma (PRP) as an alternative therapy for the treatment of erectile dysfunction. Material & Methods: We conducted a comprehensive literature search on Pubmed, Cochrane Library, ScienceDirect, Scopus, and Proquest databases for randomized controlled clinical trials (RCTs) until April 2023. The study protocol has been registered in the International Prospective Register of Systematic Reviews (PROSPERO CRD42023424586). Results: Our results showed that PRP could improve MCID in IIEF-EF score (OR: 4.64; 95% CI: 2.20, 9.79; p < 0.0001; I2 = 77%) and PSV (MD: 9.63; 95% CI: 1.17, 18.09; p = 0.03; I2 = 73%). In addition, PRP administration was shown to be relatively safe, and there was no significant difference in post-injection VAS pain scores when compared to controls (MD: -0.09; 95% CI: -0.49, 0.31; p = 0.66; I2 = 84%). Conclusion: This systematic review and meta-analysis showed promising results regarding the effects of PRP administration on erectile dysfunction. However, due to the lack of quality and number of studies, these findings should be interpreted carefully, and further investigations are still needed. Keywords: Platelet-Rich Plasma, Intracavernosal Injection, Erectile Dysfunction, IIEF-EF, Meta-Analysis.